Tariffs versus production subsidies as industry protection - Yoshitomo Ogawa; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2013)
This paper provides a welfare comparison of a tariff with a combination of a production subsidy to, and a commodity tax on, an import-competing commodity in a two-country economy. We treat some plausible situations of industry protection, including where the initial tariff is above the optimal tariff, where a certain output level of a tariff-imposed commodity must be maintained, and where there is positive externality of its domestic production. In those cases we explore the optimal combination of the production subsidy and the commodity tax and show it to be superior to the tariff from the welfare viewpoint.
Keywords: F11; F13; H23; 330; Commodity Tax; Production Subsidy; Tariff; Industry Protection; Verbrauchsteuer; Exportsubvention; Subvention; Wohlfahrtsanalyse; Zwei-Länder-Modell; Theorie